2007
DOI: 10.1061/(asce)0733-9429(2007)133:12(1421)
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Streamflow Measurements Made with Acoustic Doppler Current Profilers

Abstract: The U.S. Geological Survey and other international agencies have collaborated to conduct laboratory and field validations of acoustic Doppler current profiler ͑ADCP͒ measurements of streamflow. Laboratory validations made in a large towing basin show that the mean differences between tow cart velocity and ADCP bottom-track and water-track velocities were −0.51 and −1.10%, respectively. Field validations of commercially available ADCPs were conducted by comparing streamflow measurements made with ADCPs to refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 19 publications
0
81
0
3
Order By: Relevance
“…Studies by Morlock (1996) and Oberg and Mueller (2007) concluded that ADCP discharge measurements can be used successfully for streamflow data collection under a variety of field conditions. In Morlock (1996), 31 ADCP discharge measurements were compared to discharge ratings defined by conventional methods for the period over which the ADCP measurements were made.…”
Section: Adcp Discharge-measurement Accuracymentioning
confidence: 99%
“…Studies by Morlock (1996) and Oberg and Mueller (2007) concluded that ADCP discharge measurements can be used successfully for streamflow data collection under a variety of field conditions. In Morlock (1996), 31 ADCP discharge measurements were compared to discharge ratings defined by conventional methods for the period over which the ADCP measurements were made.…”
Section: Adcp Discharge-measurement Accuracymentioning
confidence: 99%
“…[15] Three different dimensionless times interval T d ¼ Át/T t (equation (4) [16] Even though the actual flow discharge can be accurately computed from the DNS data, the mean discharge from the 12 sampled transects in each DNS data set has been assumed to be the true discharge as is the case for field measurements (true discharge is unknown [Oberg and Mueller, 2007]). The comparison between the true discharge and the mean discharge from the 12 sampled transects of the DNS data are within 1% of difference when more than four ensembles are sampled in the cross section.…”
Section: Functional Form Obtained From Dnsmentioning
confidence: 99%
“…The calculated, statistical random uncertainty would be reduced to less than the COV if measurements consisted of at least eight transects. Collecting eight or more transects increases the total duration of the measurement, called "exposure time," which is a critical factor in reducing measurement uncertainty (Oberg and Mueller, 2007). In steady-state discharge conditions, random variability as a result of small-scale turbulence and velocity fluctuations is better represented in a measurement with a long exposure time, with limits as much as those identified in Oberg and Mueller (2007).…”
Section: Potential Opportunities For Reducing Uncertaintymentioning
confidence: 99%
“…Collecting eight or more transects increases the total duration of the measurement, called "exposure time," which is a critical factor in reducing measurement uncertainty (Oberg and Mueller, 2007). In steady-state discharge conditions, random variability as a result of small-scale turbulence and velocity fluctuations is better represented in a measurement with a long exposure time, with limits as much as those identified in Oberg and Mueller (2007). Estimated uncertainty in discharge measurements made at the Murphy streamgage was lower during the November 2012 and July 2013 seepage studies (1.1-2.1 percent) than during the period of the uncertainty evaluation in WYs 2007-11 (average 4.0 percent), partially because the seepage study measurements had more transects and longer exposure times.…”
Section: Potential Opportunities For Reducing Uncertaintymentioning
confidence: 99%